Implementation of Vehicle Accident Monitoring Device along Benin-Warri Road - Efenedo, G. I.; Egwaile, J. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Vehicle accident motoring system is a system that automatically senses an accident in real time and sends an SMS alert to predetermined numbers for rescue of accident victims. The system comprises of a designed accident detecting device to be installed in vehicles that read and interpret geographical coordinates of various locations along Benin-Warri road and GSM mobile phone. The device has a vibration sensor, GSM/GPS module with an embedded computer chip which was programmed with C language. The coordinates of the Locations were collated using GPS measuring instrument and serves as input to the device. The obtained data were subject to normality and correlation test for validation. The results show that the data are normally distributed and significant at 0.01 The device was programmed in such a way as to convert the Latitude, Longitude and Altitude of a spot to its equivalent assigned or known name.  If an accident occurs at any spot along the road, the device immediately sends the names of the location via SMS alert to relevant numbers. It was tested for the route and various successful accident alert messages were registered.